Behavioral measures of cortical hyperexcitability assessed in people who experience visual snow. (28th March 2017) - McKendrick, Allison M.; Chan, Yu Man; Tien, Melissa; Millist, Lynette; Clough, Meaghan; Mack, Heather; Fielding, Joanne; White, Owen B.
Abstract : Objective: To determine whether visual perceptual measures in people who experience visual snow are consistent with an imbalance between inhibition and excitation in visual cortex. Methods: Sixteen patients with visual snow and 18 controls participated. Four visual tasks were included: center-surround contrast matching, luminance increment detection in noise, and global form and global motion coherence thresholds. Neuronal architecture capable of encoding the luminance and contrast stimuli is present within primary visual cortex, whereas the extraction of global motion and form signals requires extrastriate processing. All these tasks have been used previously to investigate the balance between inhibition and excitation within the visual system in both healthy and diseased states. Results: The visual snow group demonstrated reduced center-surround contrast suppression ( p = 0.03) and elevated luminance increment thresholds in noise ( p = 0.02). Groups did not differ on the global form or global motion task. Conclusion: Our study demonstrates that visual perceptual measures involving the suprathreshold processing of contrast and luminance are abnormal in a group of individuals with visual snow. Our data are consistent with elevated excitability in primary visual cortex; however, further research is required to provide more direct evidence for this proposed mechanism. The ability to measure perceptual differences in visual snow reveals promise for the future development of clinical tests to assist in visual snow diagnosis and possibly a method for quantitatively assaying any benefits of treatments.